2014
DOI: 10.1038/ncomms5338
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis in Drosophila reveals age-specific effects of SNPs on fitness traits

Abstract: Most organisms exhibit senescence; a decline in physiological function with age. In nature, rates of senescence vary extensively among individuals and this variation has a significant genetic component; however, we know little about the genes underlying senescence. Here we show the first evidence that individual alleles influence fecundity in an age-specific manner and so the genetic basis of natural variation in fecundity changes dramatically with age. We complete a genome-wide association to identify single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
159
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(173 citation statements)
references
References 54 publications
(75 reference statements)
12
159
2
Order By: Relevance
“…Although little is known about the specific functions of senseless-2 , this gene was found to be differentially expressed between strains that had contrasting inbreeding effects on cold tolerance (Vermeulen et al 2013). Other SNPs at this gene have been associated with paraquat resistance and fecundity (Weber et al 2012; Durham et al 2014). senseless-2 was also predicted to regulate neuroanatomy-associated genes (Zwarts et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about the specific functions of senseless-2 , this gene was found to be differentially expressed between strains that had contrasting inbreeding effects on cold tolerance (Vermeulen et al 2013). Other SNPs at this gene have been associated with paraquat resistance and fecundity (Weber et al 2012; Durham et al 2014). senseless-2 was also predicted to regulate neuroanatomy-associated genes (Zwarts et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Functional disruption of scrib causes neoplastic overgrowth and results in manifest neuron development (Albertson and Doe 2003). In addition, scrib also contributes to variation in age-specific fitness traits, olfactory memory, and olfactory perception (Durham et al 2014; Arya et al 2015; Walkinshaw et al 2015; Cervantes-Sandoval et al 2016). DIP-η ( Dpr-interacting protein η ) is one member DIP protein family (Özkan et al 2013), whose interactions with DPR protein family were identified to form a network that is required for synaptic connectivity (Carrillo et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To map a trait of interest, a researcher can order the DGRP flies from the Bloomington Stock Center (http://flystocks.bio.indiana.edu/), measure phenotypes in these lines, and access the genome data to perform analyses (http://dgrp2.gnets.ncsu.edu/). GWAS analyses using these lines have identified significant genomic associations with sleep traits (Harbison et al 2013), life span and fecundity (Durham et al 2014), olfactory behavior (Arya et al 2015), abdominal pigmentation (Dembeck et al 2015), starvation resistance, and startle response (Mackay et al 2012;Ober et al 2012). In several cases, the genes identified in these studies have orthologs implicated in similar phenotypes in humans (e.g., Harbison et al 2013).…”
Section: Evolutionary Genetics and Molecular Evolutionmentioning
confidence: 99%